Implementation of Reproductive Services With Assistance - Arief Santoso; Sutarno Sutarno; Budi Pramono (Jurnal Indonesia Sosial Sains, 2025)
Problems for infertile couples are currently being answered with the advancement of Assisted Reproductive Technology (ART) which is experiencing a leap of innovation in medical science for handling infertility problems and reproductive challenges. assisted reproduction in Indonesia. This research is normative legal research with statutory, conceptual and comparative approaches. This research also highlights the role of health institutions, practitioners and policy makers in ensuring equitable provision of ART services while respecting cultural and religious values. The research results show that although Indonesia has basic regulations, further improvements are needed to adapt to advances in ART technology and community needs. The lack of harmonization of regulations between countries has led to legal uncertainty regarding the status of children resulting from assisted reproduction, especially in cross-country cases.